Laboratory Investigations of Extrasensory Identification of Concealed 5-Character Codes by a Presumably Gifted Teenager - Shen, Dong; Shen, Run-Sheng; Li, Gang (Journal of Scientific Exploration, 2021)
We report on laboratory investigations of extrasensory identification of object information against a visual sensory barrier conducted on a presumably gifted teenage female subject in China. The investigations challenged the subject to identify a 5-character code (black, bold, Arial, font size 14) prepared by a double-blind procedure and sealed to block ordinary sensory access. Each of the five characters of each sealed code were randomly generated by computer permutation among 34 choices, including capitalized letters of A to Z and numbers from 2 to 9, by a third party at a remote site before mailing to the examiner. The subject’s attempts to identify, via self-claimed extrasensory means, the concealed 5-character code over the duration of each trial was monitored and videorecorded. Trials of 16 and 18 tests were conducted approximately three months apart. Of the total 34 trials, the subject made a full hit (i.e. five correct characters at the entirely correct sequence) five times, corresponding to a binomial probability of p < 0.00001. We conclude that extrasensory identification against a visual sensory barrier deserves further investigation. Keywords: Clairvoyance, extrasensory perception (ESP), extrasensory identification (ESI), altered or alternative state of consciousness (ACS), second consciousness state (SCS)